Kejahatan Teknologi Informasi (Cyber Crime) dan Penanggulangannya dalam Sistem Hukum Indonesia - Miftakhur Rokhman Habibi; Isnatul Liviani (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
This article aims to let us learn more about cyber crime. This is due to the weakness of cyberspace can become a global disaster that threatens the business sector, national and global security, behavior, child protection, and government systems. The results showed that the public is currently still misusing social media to spread crime in cyberspace. Most of the perpetrators of cybercrime on social media will be caught by Law No.11 of 2008 concerning Electronic Information and Transactions (UU ITE), whether intentional or unintentional. The law should provide protection for internet users with good intentions, and provide firm action for perpetrators of cyber crime. However, the legal system has not solved all computer crimes over the Internet. Likewise in the investigation, there were many obstacles related to legal instruments, the ability of investigators, evidence, and computer forensic facilities. This is why cyber crime law enforcement is still weak.